The Relationship Between Business Environment and Single Champion Enterprise Entrepreneurship - Wu, Chanti; Lin, Jinjin (Frontiers in Psychology, 2022)
What kind of business environment can produce high single champion enterprise entrepreneurship is a new issue for discussion in research on entrepreneurship. Based on institutional configuration theory and the fcQCA method, the present paper analyses the relationship between the business environment and single champion enterprise entrepreneurship from the perspective of configuration. This paper studies the role of the business environment in 80 case cities all over the country in promoting high single champion enterprise entrepreneurship and discusses three business environment configurations concerning high single champion enterprise entrepreneurship and two configurations concerning non-high single champion enterprise entrepreneurship. Three typical business environment element configurations can promote high single champion enterprise entrepreneurship, namely, the market innovation type dominated by multiple resources, the financial service–driven type assisted by resources, and the market-driven type led by financial services, which reflects the significance of financial services and the market environment.